Assessment of school performance of preschool children in CEAPE program - Pontieri, Maria José; Cavalcanti, Maria Lúcia Ferrari; Gandra, Yaro R. (Revista de Saúde Pública, 1981)
The scholastic performance of subjects who attended the CEAPE program as compared to a control group belonging the same community which did not attend the program, is assessed. It was demonstrated that performance in 1st and 2nd grades was significantly better for those students involved in the program. Therefore besides differences in socio-psycho-motor development demonstrated in former studies, the CEAPE, although simple and inexpensive, also garantees better scholastic performance to those attending the program.